A novel multi-terminal fuzzy-logic controlled IUPQC device for power quality enhancement in multi-feeder distribution systems - Venna Jaya Lakshmi; Katragadda Swarnasri (Institute of Advanced Engineering and Science, 2026)
Non-linear sensitive loads are increasingly being used in a wide range of industrial and home applications. Particularly, some nonlinear sensitive loads degrade the power quality (PQ) of a multi-feeder distribution system by causing current as well as voltage quality to deviate from normal standards. To address these PQ issues, a unique multi-terminal interline unified power quality conditioner (MT-IUPQC) device has been implemented in a multi-feeder distribution system. This MT-IUPQC is made up of multi-voltage source inverters (VSI) coupled by a common direct current (DC)-linked capacitor, and which is controlled by using proportional integral (PI) control method. However, due to an inappropriate gain setting choice, this PI is not suitable for regulating the DC voltage at the specified voltage level. In this paper, an intelligent fuzzy-logic controlled MT-IUPQC provides an intelligent knowledge set with subjective assessments for improved mitigation of PQ difficulties. The recovered total harmonic distortion (THD) of source current is 2.45%, 2.71%, which are well within IEEE-519/2014 norms and significantly lower than the THD of non-linear sensitive load current of 30.19%, 30.05% in both feeder-1 and 2. In a similar way, the THD of non-linear sensitive load voltage is obtained at 0.43%, which fits well under IEEE-519/2014 norms and is significantly lower than the THD of the voltage source measured at 20.62% in feeder-1.